New perspectives on mobbing in banking institutions - El-Aouar, Walid Abbas; Patriota, Renata Almeida de Lucena; Silva, Arthur William Pereira da; Veiga Neto, Alípio Ramos; Castro, Ahiram Brunni Cartaxo de; Mesquita, Rafael Fernandes de; Barreto, Laís Karla da Silva (Revista de Administração da UFSM, 2020)
The objective of this research was to diagnose bullying based on the perception of the occurrence of the phenomenon by employees of public and private banking institutions in the city of João Pessoa, state of Paraíba, Brazil. It is a descriptive research and a case study with a quantitative approach applied to a simple random sample of 156 bank clerks, through a sociodemographic questionnaire and a perception scale of mobbing at work, validated by Martins and Ferraz (2014). Data were analyzed by using the SPSS software and compared by Chi-square tests and variance analysis. There was an equal participation concerning gender, most of them from white ethnicity, married, graduates, and mean age of 39 years. It was found that the phenomenon was perceived infrequently, at least once a month. 34% of bank clerks reported professional harassment and 19.9% reported personal harassment. Such results prompted reflection on whether the phenomenon was overcome, reduced or trivialized among the professional category studied. The results also showed that, although perceived infrequently, harassment behavior is more observed with employees in private banks than in public ones.